Theoretical reflections on research in educational policys. Epistemologies of Education Policy Approach - Tello, César (Advances in Social Sciences Research Journal, 2014)
This paper intends to introduce a theoretical reflection on the epistemological perspectives used in education policy research and the way in which those perspectives greatly influence the definition of the object of the theoretical field using the analytical category of the Epistemology of Education Policy Approach as a basis for analysis, leaving aside the State focused classical definition of the object of study of education policy. The premises assumed on this paper are, on the one hand, considering that education policy as a theoretical field is defined through the perspective and epistemological positioning of the person who interprets/characterizes it and, on the other hand, that that definition from a specified epistemological positioning responds to an episteme of epoch in terms of Foucault.